Antimicrobial activity of natural products against MDR bacteria: A scientometric visualization analysis - Zhou, Yan-Xi; Cao, Xiao-Yu; Peng, Cheng (Frontiers in Pharmacology, 2022)
Methods: All relevant original articles and reviews for the period 1997 - 2021 were retrieved from the Web of Science Core Collection database. VOSviewer, a scientometric software, and an online bibliometric analysis platform were used to conduct visualization study. Results: A total of 1,267 papers were included, including 1,005 original articles and 262 reviews. The United States and India made the largest contribution in this field. The University of Dschang from Cameroon produced the most publications. Coutinho HDM, Kuete V, and Gibbons S were key researchers, as they published a great many articles and were co-cited in numerous publications. Frontiers in Microbiology and Antimicrobial Agents and Chemotherapy were the most influential journals with the highest number of publications and co-citations, respectively. “Medicinal plants”, “methicillin-resistant Staphylococcus aureus”, “biofilm”, “MIC”, and “efflux pumps” were the most frequently used keywords, so these terms are presumed to be the current hot topics. All the included keywords could be roughly divided into four major themes, of which the theme of “natural product development approach” had attracted much attention in recent years. Furthermore, “Pseudomonas aeruginosa”, “nanoparticles”, “green synthesis”, “antimicrobial peptides”, “antibiofilm”, “biosynthetic gene clusters”, and “molecular dynamics simulation” had the latest average appearance year, indicating that these topics may become the research hot spots in the coming years. Conclusion: This study performed a scientometric analysis of the antibacterial activity of natural products against multidrug-resistant bacteria from a holistic perspective. It is hoped to provide novel and useful data for scientific research, and help researchers to explore this field more intuitively and effectively.